The Reading of William Blake’s (1757-1827) “London”: A Discourse Analysis Approach - Ngitsi, Barnabé Katsuva (Indian Journal of Language and Linguistics, 2024)
This study has attempted to investigate the problem faced by children in an aristocratic or well-to-do society. Through the narrator’s language, it has been proven that the pretenders do not care of the low class. The former are Londoners together with the leaders who have marginalized the proletarians or the working class: women, soldiers, artists, teachers, sweepers, and so on. These people are considered not only as children but they are also not seen because they are mere faces, i.e. the invisible people who have nothing to say in decision making. In addition, the Church leaders in London seem to preach what they are not able to live, for they are, instead of preaching the gospel, involved in murder (hearse) and in insanity. As they are also involved in politics, they pass laws and make charters for useless matters such as rivers and streets ignoring children and other vulnerable people.